THE EFFECTS OF POVERTY ON THE HUMAN PSYCHE REFLECTED IN RUPERT BROOKE’S LITHUANIA: A PSYCHOANALYTIC STUDY - Irwan Sumarsono (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2023)
This study analyzes the psychological effects of poverty on individuals using Rupert Brooke's play,